Supporting dataset and methods for Transplacental Transfer of Organochlorine Pesticides: Concentration Ratio and Chiral Properties - Shanshan Yin; Jianyun Zhang; Fangjie Guo; Lu Zhao; Giulia Poma; Adrian Covaci; Weiping Liu (Data in Brief, 2019)
The dataset and methods provided in this article supports “Transplacental Transfer of Organochlorine Pesticides: Concentration Ratio and Chiral Properties” [1]. The supplementary data were as follows: 1) the information on pretreatment and instrumental methods.2) the data for concentration in the maternal serum, cord serum and placenta samples and data interpretation. 3) the correlation between the influence factors and the log-transformed concentrations of the chemicals samples. 4) the dataset for transplacental transfer ratio of the OCPs and correlations with influencing factors. Keywords: Placental transfer, Organochlorine pesticides, Human biomonitoring, Enantiomeric fractions